Pengaruh Dana Pihak Ketiga, LDR, BOPO Terhadap ROA Pada Bank Umum Swasta Nasional Periode 2012-2016 - Bonifasius Hamonangan Tambunan (Journal of Economic and Business, 2020)
This research was conducted to examine the effect of Third Party Funds (DPK), Loan to Deposit Ratio (LDR) and Operational Cost of Operating Income (BOPO) on Return on Assets (ROA). This research is a quantitative study that is research data in the form of numbers or qualitative data called scoring. The data used in this study was obtained from the annual Publication Financial Reports of the Public Banking that were listed on the Indonesia Stock Exchange for the 2012-2016 period published by Bank Indonesia. After going through the purposive sample stage, the samples used were 9 companies as observations go public banking listed on the IDX. The method used in this research is multiple regression analysis. The results obtained indicate that DPK does not significantly affect ROA. LDR and BOPO significantly influence ROA. Keyword: Third Party Funds (DPK), Loan to Deposit Ratio (LDR), Operational Income Operating Cost (BOPO), Return on Asset (ROA).